2006
DOI: 10.1002/hc.20174
|View full text |Cite
|
Sign up to set email alerts
|

6-Polyfluoroacyl- and 6-trichloroacetylnorkhellins: Synthesis and reaction with aromatic amines

Abstract: Five new 6-polyhaloacylnorkhellinswere synthesized in high yields from diethoxymethyl acetate and the condensation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…We prepared a series of 3‐methoxalylchromones 1a – d , 3‐aroylchromones 2a – h , and 3‐cinnamoylchromone 3 starting from readily accessible 3‐(dimethylamino)‐1‐(2‐hydroxyaryl)prop‐2‐en‐1‐ones by using a one‐pot acylation procedure (Table ) , , . Almost all the chromones used in this study were reported and described in our previous work , …”
Section: Resultsmentioning
confidence: 99%
“…We prepared a series of 3‐methoxalylchromones 1a – d , 3‐aroylchromones 2a – h , and 3‐cinnamoylchromone 3 starting from readily accessible 3‐(dimethylamino)‐1‐(2‐hydroxyaryl)prop‐2‐en‐1‐ones by using a one‐pot acylation procedure (Table ) , , . Almost all the chromones used in this study were reported and described in our previous work , …”
Section: Resultsmentioning
confidence: 99%
“…232 Reactions of 3-polyfluoroacylchromones 154 with primary aliphatic and aromatic amines occur as 1,4-addition followed by opening of the pyran ring and cyclization to 3-alkyl(aryl)aminomethylidene-2-hydroxy-2-polyfluoroalkylchroman-4-ones 158. 233,234,238 6-Polyfluoroacylnor-kellins 154 (R 2 ± R 3 = OCH = CH) react with aliphatic amines (cyclohexylamine and benzylamine) to form only mixtures of unidentified products. 233 The reaction of 3-formylchromones with primary aromatic amines results in a mixture of 3-aryliminomethylchromone and 2-arylamino-3-arylaminomethylidenechroman-4-one that was difficult to separate.…”
Section: Reactions Of 3-polyfluoroacylchromonesmentioning
confidence: 99%
“…233,234,238 6-Polyfluoroacylnor-kellins 154 (R 2 ± R 3 = OCH = CH) react with aliphatic amines (cyclohexylamine and benzylamine) to form only mixtures of unidentified products. 233 The reaction of 3-formylchromones with primary aromatic amines results in a mixture of 3-aryliminomethylchromone and 2-arylamino-3-arylaminomethylidenechroman-4-one that was difficult to separate. 239 The result of the reaction of 3-trifluoroacetylchromones 154 with ethylenediamine and o-phenylenediamine depends on the reaction conditions and the nature of the substituent in the benzene ring of chromone.…”
Section: Reactions Of 3-polyfluoroacylchromonesmentioning
confidence: 99%